A Rare Case of Primary Sarcoma Arising Within Free Muscle Transfer - Anchal Jain; Bilal Rafique; Amer J. Durrani; Ahid Abood (Archives of Plastic Surgery)
Soft tissue sarcomas are one of the rarest forms of cancer. We describe a unique case of a 35-year-old patient who sustained an open lower limb fracture requiring an intramedullary nail and free latissimus dorsi (LD) muscle flap reconstruction. He had a complex postoperative course including osteomyelitis, a refracture, and chronic pain. Eleven years following the injury, he presented with pain and localized swelling around the flap. Histological analysis confirmed a rhabdomyosarcoma within the LD muscle and he underwent a transfemoral amputation. He is now in remission and walks on a prosthesis pain-free.